Niki's Moonchild Album: A Study of Figurative Language - Adhi Kusuma; Verisa Rania Nurfitri; Ima Widyastuti; Victa Sari Dwi Kurniati; Zohaib Hassan Sain (Universitas Sarjanawiyata Tamansiswa, 2024)
The study aims to identify the specific types of figurative language employed in Niki's chosen songs, as well as the most prevalent types of figurative language observed in those songs. The researchers utilized a descriptive qualitative research methodology to examine and analyze the song lyrics. This research focuses on analyzing the selected song lyrics from Niki's Moonchild album. Through this investigation, various forms of figurative language have been recognized within the context of Kennedy, X.J. and Gioia, D.'s theory. The following are examples of figurative language: personification, metaphor, simile, hyperbole, synecdoche, irony, contradiction, repetition, apostrophe, and allegory. Furthermore, it unveiled the prevailing form of metaphorical language that was employed universally. The lyrics chosen from Niki's Moonchild album employ metaphors extensively, representing the most often recognized type.